Effects of kerosene heating on dynamic characteristics of GOx/kerosene combustor. (September 2016) - Song, Wooseok; Kim, Dohun; Lee, Keonwoong; Shin, Bongchul; Ko, Sangho; Koo, Jaye
Abstract: The objective of this study was to observe low-frequency instabilities caused by heating of kerosene under supercritical operating conditions. Gaseous oxygen and liquid kerosene were injected using a shear-coaxial injector. Under specific heating conditions, the fuel heating system induced an extremely low frequency pressure fluctuation ranging from 9.9 to 11.4 Hz. When pressure oscillation occurred in the heating system, low-frequency combustion instability was subsequently induced in the range of 30–200 Hz. To understand the effects of the fuel heating temperature on the combustion instability, the dynamic pressure and OH* chemiluminescence intensity were measured in a combustion chamber at high speed. Further, the reacting spray of the combustion was visualized by a shadowgraph technique. In this experiment, an approximate fuel pressure of 3.0 MPa was employed in order to attain a supercritical condition of kerosene. The measured dynamic pressure and chemiluminescence intensity in the time domain were converted to frequency-domain spectra by fast Fourier transform. Analysis of the dynamic pressure and chemiluminescence intensity measurements confirmed that the low-frequency pressure oscillation in the heating system had an influence on the combustion instability. From the visualization data, it was also revealed that there existed varying amplitude levels of flow rate fluctuation. This fluctuation in turn caused a periodic injection of kerosene at a frequency similar to both the combustion instability frequency and the OH* chemiluminescence intensity frequency. Highlights: Acoustic droplet vaporization caused combustion instability under high fuel temperature. The combustion instability intensity increased with an increase in the fuel temperature. Fuel instability is the reason of the sound wave produced by a choked flow in an orifice.